Preparation method and application of absorbable zinc alloy membrane material

By adding isochannel angle extrusion technology and multiple heat treatments to the preparation process of zinc alloy film, the problems of poor strength and poor biocompatibility of existing zinc alloy films are solved, and zinc alloy film materials with ultrafine grain structure and significantly improved strength and biocompatibility are prepared.

CN119876660APending Publication Date: 2025-04-25YUEMEI BIOTECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411846316.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing zinc alloy film preparation process results in the micron-level grains of the zinc alloy film, poor strength and poor biocompatibility.

Method used

Intermediate alloys and primary zinc alloy metals are prepared by smelting method, and zinc alloy metals with ultrafine grain structures are obtained through isochannel angle extrusion technology, followed by free forging, rough rolling and foil rolling to obtain an absorbable zinc alloy film material.

Benefits of technology

The prepared zinc alloy membrane material has an ultrafine grain structure, with a strength of more than three times and significantly improved biocompatibility. It is suitable as an absorbable tissue repair membrane to promote tissue healing, antibacterial, anti-osteoporosis and anti-atherosclerosis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876660A_ABST
    Figure CN119876660A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an absorbable zinc alloy membrane material, and relates to the technical field of metal processing.The preparation method comprises the steps that zinc and alloy metal are smelted to prepare intermediate alloy; smelting the intermediate alloy and zinc to obtain primary zinc alloy metal; performing an equal-channel angular extrusion process on the primary zinc alloy metal to obtain zinc alloy metal, wherein the zinc alloy metal has an ultra-fine grain structure; and the zinc alloy metal is subjected to free forging, rough rolling and foil rolling, and then the absorbable zinc alloy membrane material is obtained. Compared with a common pure zinc film, the tensile strength of the zinc alloy film is improved by more than three times by using a set of brand new process and formula combination, and the material still has the elongation percentage of more than 20% so as to meet the requirements of the material on the design of medical instrument products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of an absorbable zinc alloy film material and application thereof, belonging to the technical field of metal processing. Background Art

[0002] Metallic zinc is considered to have the potential to become the next generation of absorbable medical implant materials. Zinc is one of the essential trace elements for the human body. It is involved in many physiological processes and biochemical reactions, and plays an important role in the function of the human immune system, cell growth and division, protein synthesis, and nervous system function. Although magnesium (Mg) and iron (Fe)-based alloys have been widely studied in the past two decades, they have always had their own limitations in the field of implantable medical devices, such as the rapid degradation of magnesium-based alloys, the accumulation of hydrogen after hydrogen evolution reaction around the tissue, and the residual ferric oxide in the body after the degradation of iron-based alloys. Can not be metabolized, etc. Zinc (Zn)-based alloys are introduced as alternative materials to overcome the limitations of Fe and Mg-based alloys.

[0003] Zinc-based alloys can produce alloys with adjustable mechanical properties and corrosion rates by blending different alloying elements and processing conditions, which is particularly important for cardiovascular and orthopedic devices. Zinc is a promising bioresorbable implant material with a more moderate degradation rate compared to magnesium and iron. Zinc's biocompatibility and biodegradability make it a potential material for cardiovascular stents and orthopedic implants. Completely dissolved bioresorbable implants help tissue healing and leave no implant residues in the surrounding tissues. In addition, zinc alloys also have antibacterial effects, which are very important for reducing the risk of implant-related infections. Its unique effect of stimulating bone growth is particularly advantageous as an orthopedic implant material.

[0004] The traditional zinc alloy film preparation process generally adopts multiple rolling processes directly after melting to form a film. The grains of the zinc alloy film prepared in this way are at the micron level, and the strength and biocompatibility are poor. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an absorbable zinc alloy film material and its application, which can prepare an absorbable film material composed of a zinc alloy metal with an ultrafine grain structure, thereby improving the mechanical properties and biocompatibility of the film material.

[0006] To achieve the above object, the present invention is implemented by adopting the following technical solutions: In one aspect, the present invention provides a method for preparing an absorbable zinc alloy film, comprising: The zinc and the alloy metal are smelted to prepare a master alloy; The master alloy and zinc are smelted to obtain primary zinc alloy metal; Performing an equal channel angular extrusion process on the primary zinc alloy metal to obtain a zinc alloy metal having an ultrafine grain structure; The absorbable zinc alloy film material is obtained by free forging, rough rolling and foil rolling of the zinc alloy metal.

[0007] Furthermore, the alloy metal includes one or more of magnesium, iron, copper, calcium, manganese, phosphorus, lithium, and silver. The mass ratio of zinc in the zinc alloy metal is 90%-99.99%, the mass ratio of the alloy metal is 0.01~10%, and the mass ratio of the alloy metal in the intermediate alloy accounts for 1~20%.

[0008] Furthermore, the preparation of the intermediate alloy by smelting zinc and alloy metal and the smelting of the intermediate alloy and zinc to obtain the primary zinc alloy metal include: Laying part of the zinc on the bottom of the heating furnace, then laying the alloy metal or the master alloy on the zinc, and then laying the remaining part of the zinc on the alloy metal or the master alloy; Under vacuum, the temperature in the furnace is raised to 210-250°C, then stepwise raised to 630-670°C, then lowered to 440-560°C, stirred until the temperature of the molten metal no longer changes, and cooled to obtain an intermediate alloy or primary zinc alloy metal.

[0009] Furthermore, the process of subjecting the primary zinc alloy metal to an equal channel angular extrusion process to obtain the zinc alloy metal comprises: According to an equal channel angular extrusion die, the primary zinc alloy metal is made into a block sample suitable for the equal channel angular extrusion die, wherein the equal channel angular extrusion die is composed of two intersecting equal diameter channels, and the equal diameter channels are rotatably connected; The block sample is placed in an equal channel angular extrusion die, and pressure is applied to the block sample at a constant speed using a punch so that the block sample is pressed into another channel of the equal channel angular extrusion die. The equal diameter channel is rotated and the pressure application operation is repeated multiple times to obtain a zinc alloy metal.

[0010] Furthermore, the angle range of the intersection of the two equal-diameter channels in the equal-channel angular extrusion die is 90° to 120°; The equal channel angular extrusion process parameters include: a temperature range of 220-300°C, an extrusion ratio of 15-100, an extrusion speed of 0.1-5 mm / s, a maximum working pressure of the main cylinder liquid controlled within 22 MPa, and an extrusion angle of 60-90°.

[0011] Furthermore, the method also includes lubricating the inner wall of the equal channel extrusion die.

[0012] Furthermore, the free forging comprises: maintaining the zinc alloy metal at 160-200° C. in a heating furnace for 2-4 hours, performing free forging at 100-280 tons, and annealing to 260° C. to obtain a zinc alloy cake.

[0013] Furthermore, the rough rolling is used to reduce the thickness of the zinc alloy cake to 1 mm, which includes multiple first cold crushing stages, wherein the first cold crushing stage includes reducing the thickness of the zinc alloy cake by 1-4 mm, annealing to 200-240° C., and cooling with the furnace.

[0014] Furthermore, the foil rolling is used to reduce the thickness of the zinc alloy cake to 10-100 μm, which includes multiple second cold-smashing stages, wherein the second cold-smashing stage includes reducing the thickness of the zinc alloy cake by 0.02-0.5 mm, annealing to 200-240° C., and cooling with the furnace.

[0015] On the other hand, the present invention also provides an application of an absorbable zinc alloy film material prepared by the preparation method of the absorbable zinc alloy film material as described in any of the above items, including a metal layer as an absorbable tissue repair membrane, wherein the absorbable tissue repair membrane is used to promote tissue healing, antibacterial, anti-osteoporosis and anti-atherosclerosis.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The zinc alloy metal prepared by the preparation process of the present invention has an ultrafine grain structure, and the grains are evenly distributed, and the grain size is between 200 and 300 nanometers, which greatly improves the strength of the zinc alloy film, and cooperates with multiple heat treatment and annealing processes to reduce processing plasticity, so that the steel strength of the film material can be guaranteed, and the film material will not become brittle, and has a certain toughness; The zinc alloy film material prepared by the present invention has a tensile strength that is more than three times higher than that of ordinary pure zinc film, and the material is still guaranteed to have an elongation of more than 20% to meet the material requirements for medical device product design. The tissue repair membrane is widely used in medical treatments such as dental implants, maxillofacial surgery, cesarean section, and neurosurgery, and can cover wounds, avoid infection, stimulate local tissue growth, and shield and guide bone growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM schematic diagram of the zinc alloy film in Example 1 of the present invention at a magnification of 50 times; Figure 2 This is a SEM schematic diagram of the zinc alloy film in Example 1 of the present invention at a magnification of 1500 times; Figure 3 Schematic diagram of the mechanical property curve of the zinc alloy film in Example 1 of the present invention; Figure 4Schematic diagrams showing the comparison of the zinc alloy film in Example 1 of the present invention before and after being placed in the simulated body fluid SBF solution for one week, wherein a is a SEM schematic diagram of the zinc alloy film before being placed in the simulated body fluid SBF solution, and b is a SEM schematic diagram of the zinc alloy film after being placed in the simulated body fluid SBF solution for one week; Figure 5 This is a schematic structural diagram of the medium channel angular extrusion die in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0019] The embodiment of the present invention provides a method for preparing an absorbable zinc alloy film material. In this embodiment, the film material is a zinc-magnesium alloy. The preparation method specifically includes the following steps: The first step is to prepare the master alloy by smelting zinc and magnesium First, spread the zinc all over the bottom of the furnace, then stand the magnesium blocks sawed into small sections upright and put them into the furnace, and then add all the remaining zinc into the furnace.

[0020] Under vacuum, the temperature in the furnace is raised to 230°C and then stepwise increased to 650°C, with each temperature increase of about 10°C. The temperature is then lowered to 460°C and stirred until the temperature of the molten metal no longer changes. The intermediate alloy is then obtained by cooling.

[0021] The second step is to smelt the master alloy and zinc to obtain the primary zinc alloy metal First, spread the zinc all over the bottom of the furnace, then stand the intermediate alloy that has been sawed into small sections upright and put it into the furnace, and then add all the remaining zinc into the furnace.

[0022] Under vacuum, the temperature in the furnace is raised to 230°C and then stepwise increased to 650°C, with each temperature increase of about 10°C. The temperature is then lowered to 460°C and stirred until the temperature of the molten metal no longer changes. The primary zinc alloy metal is cooled to obtain the primary zinc alloy metal. In this embodiment, the primary zinc alloy metal material is 80 mm high and 47 mm in outer diameter.

[0023] The third step is to perform equal channel angular extrusion process on the primary zinc alloy metal to obtain zinc alloy metal like Figure 5 As shown, an equal channel angular extrusion die is prepared. The equal channel angular extrusion die consists of two intersecting equal diameter channels. The equal diameter channels can rotate around the corner. In this embodiment, the corner angle of the equal channel angular extrusion die is 100°.

[0024] The primary zinc alloy metal is formed into a block specimen of a suitable equal channel angular extrusion die so that the channel size of the die is almost equal to the cross-sectional size of the block specimen.

[0025] Ensure that the inner wall of the equal channel angular extrusion die is well lubricated to reduce friction and improve metal fluidity.

[0026] The block sample is placed in an equal channel angular extrusion die, and a punch is used to press the block sample into the channel at a constant speed, so that the block sample undergoes uniform and severe shear deformation at the corner. In this embodiment, the parameters for applying pressure are controlled as follows: the temperature range is 260°C, the extrusion ratio is 30, the extrusion speed is 2mm / s, the maximum working pressure of the main cylinder liquid is controlled at 20Mpa, the high extrusion ratio of 90° is used in the early stage, and the low extrusion ratio of 60° is used for discharge in the later stage.

[0027] The channel is rotated at a certain angle and the above pressure application operation is repeated multiple times to accumulate and superimpose the deformation to obtain a larger deformation, thereby achieving grain refinement.

[0028] Zinc alloys with ultrafine grain structures can be obtained through the equal channel angular extrusion process, which significantly improves the mechanical properties and biocompatibility of zinc alloys, which is of great significance for the development of high-strength and uniform elongation zinc alloys as biomedical devices.

[0029] Step 4: Free forging, rough rolling and foil rolling of the zinc alloy metal to obtain absorbent zinc alloy film material Free forging includes: The first stage of cold hammering (from 10 to 8 mm) requires a mold replacement and annealing; The second stage of cold hammering (from 8 to 4 mm) requires replacement of secondary molds and annealing; The third stage of cold hammering (from 3 to 1 mm) requires replacement of secondary molds and annealing; Finally, foil rolling is performed, including: The first stage of cold hammering (from 1 mm to 0.5 mm) requires replacement of secondary molds and annealing; The second stage of cold hammering (from 0.5 mm to 0.1 mm) requires replacement of secondary molds and annealing; The third stage of cold hammering (from 0.1 mm to 0.06 mm) requires replacement of secondary molds and annealing; The fourth stage of cold hammering (from 0.1 mm to 0.03 mm) requires replacement of the secondary mold and annealing.

[0030] It should be noted that the cold hammering needs to be kept in the same direction, and the annealing treatment is unified as annealing to 260°C and cooling with the furnace for 24 hours. The preparation of the intermediate alloy first and then the absorbable zinc alloy film material can ensure the uniform distribution of magnesium.

[0031] The microstructure of the absorbable zinc alloy membrane finally prepared is as follows Figure 1 and Figure 2 As shown, it can be seen Figure 1There are many white crystals in the film, which are the second image of magnesium, which proves the uniform preparation of the zinc alloy film. Figure 2 It can be seen that the zinc alloy has an ultrafine grain structure, satisfying that all grain sizes are within 10 microns, and some grain sizes are between 200 and 300 nanometers.

[0032] The mechanical properties of absorbable zinc alloy membranes are as follows Figure 3 As shown, it can be seen that the zinc alloy film has good mechanical properties.

[0033] The zinc alloy film was immersed in the simulated body fluid SBF solution for one week. The SEM images before and after immersion were as follows: Figure 4 a and Figure 4 As shown in b, it can be seen from the comparison in the figure that the surface of the zinc alloy film was severely corroded after being immersed in the simulated body fluid SBF solution for one week, which effectively proves that the zinc alloy film is degradable and can be completely metabolized by the human body after completing the reconstruction of blood circulation physiological functions in the human body.

[0034] The biocompatibility of the prepared zinc alloy film material is analyzed below. The biocompatibility analysis adopts cytotoxicity, sensitization test, intracutaneous reaction, acute systemic toxicity, genetic toxicity, subchronic systemic toxicity, and local reaction test after implantation-bone implantation test. The test basis is shown in Table 1.

[0035] Table 1: Biocompatibility-related test basis

[0036] The test results are shown in Table 2.

[0037] Table 2: Biocompatibility related test results

[0038] It can be seen from Table 2 that the biological evaluation test results of the zinc alloy film material prepared by the present invention meet the standard requirements, the biological risk is within an acceptable range, and it has biocompatibility.

[0039] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an absorbable zinc alloy film, characterized in that: include: The zinc and the alloy metal are smelted to prepare a master alloy; The master alloy and zinc are smelted to obtain primary zinc alloy metal; Performing an equal channel angular extrusion process on the primary zinc alloy metal to obtain a zinc alloy metal having an ultrafine grain structure; The absorbable zinc alloy film material is obtained by free forging, rough rolling and foil rolling of the zinc alloy metal.

2. The method for preparing the absorbable zinc alloy film according to claim 1, characterized in that: The alloy metal includes one or more of magnesium, iron, copper, calcium, manganese, phosphorus, lithium and silver. The mass of zinc in the zinc alloy metal accounts for 90%-99.99%, the mass of the alloy metal accounts for 0.01-10%, and the mass of the alloy metal in the intermediate alloy accounts for 1-20%.

3. The method for preparing the absorbable zinc alloy film according to claim 1, characterized in that: The method of preparing a master alloy by smelting zinc and an alloy metal and obtaining a primary zinc alloy metal by smelting the master alloy and zinc comprises: Laying part of the zinc on the bottom of the heating furnace, then laying the alloy metal or the master alloy on the zinc, and then laying the remaining part of the zinc on the alloy metal or the master alloy; Under vacuum, the temperature in the furnace is raised to 210-250°C, then stepwise raised to 630-670°C, then lowered to 440-560°C, stirred until the temperature of the molten metal no longer changes, and cooled to obtain an intermediate alloy or primary zinc alloy metal.

4. The method for preparing the absorbable zinc alloy film according to claim 1, characterized in that: The method of subjecting the primary zinc alloy metal to an equal channel angular extrusion process to obtain the zinc alloy metal comprises: According to an equal channel angular extrusion die, the primary zinc alloy metal is made into a block sample suitable for the equal channel angular extrusion die, wherein the equal channel angular extrusion die is composed of two intersecting equal diameter channels, and the equal diameter channels are rotatably connected; The block sample is placed in an equal channel angular extrusion die, and pressure is applied to the block sample at a constant speed using a punch so that the block sample is pressed into another channel of the equal channel angular extrusion die. The equal diameter channel is rotated and the pressure application operation is repeated multiple times to obtain a zinc alloy metal.

5. The method for preparing the absorbable zinc alloy film according to claim 4, characterized in that: The angle range of the intersection of two equal-diameter channels in the equal-channel angular extrusion die is 90° to 120°; The equal channel angular extrusion process parameters include: a temperature range of 220-300°C, an extrusion ratio of 15-100, an extrusion speed of 0.1-5 mm / s, a maximum working pressure of the main cylinder liquid controlled within 22 MPa, and an extrusion angle of 60-90°.

6. The method for preparing the absorbable zinc alloy film according to claim 4, characterized in that: It also includes lubricating the inner wall of the equal channel extrusion die.

7. The method for preparing absorbable zinc alloy film according to claim 1, characterized in that: The free forging comprises: maintaining the zinc alloy metal at 160-200° C. for 2-4 hours in a heating furnace, performing free forging at 100-280 tons, and annealing to 260° C. to obtain a zinc alloy cake.

8. The method for preparing absorbable zinc alloy film according to claim 1, characterized in that: The rough rolling is used to reduce the thickness of the zinc alloy cake to 1 mm, which includes multiple first cold crushing stages. The first cold crushing stage includes annealing to 200-240° C. after reducing the thickness of the zinc alloy cake by 1-4 mm and cooling with the furnace.

9. The method for preparing absorbable zinc alloy film according to claim 1, characterized in that: The foil rolling is used to reduce the thickness of the zinc alloy cake to 10-100 μm, which includes multiple second cold-smashing stages. The second cold-smashing stage includes reducing the thickness of the zinc alloy cake by 0.02-0.5 mm, annealing to 200-240° C., and cooling with the furnace.

10. An application of an absorbable zinc alloy film material prepared by the method for preparing an absorbable zinc alloy film material according to any one of claims 1 to 9, characterized in that: The invention comprises a metal layer as an absorbable tissue repair membrane, wherein the absorbable tissue repair membrane is used for promoting tissue healing, antibacterial, anti-osteoporosis and anti-atherosclerosis.